Eksplorasi Nilai Budaya ‘Siri’ pada Perilaku Konsumsi dalam Perspektif Ekonomi Syariah: Studi Kasus pada Komunitas Muslim antar Generasi di Watampone - Vera Rahmayanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to explore the meaning of the Bugis cultural value of siri’ and its role in shaping the consumption behavior of Muslim communities in Watampone, viewed from the perspective of Islamic economics. Using a qualitative exploratory approach, data were collected through in-depth interviews with informants from different generations—Baby Boomers, Generation X, Millennials, and Gen Z—to examine the evolving interpretation of siri’ across time. The findings show that siri’ is understood differently by each generation. Older generations perceive it as a strong form of social control and collective honor, while younger generations tend to associate siri’ with social prestige—or in some cases, it has shifted into a consumptive impulse that strays from its original meaning. In the context of consumption, siri’ often influences purchasing decisions, particularly in communal events such as weddings, choice of products, and the display of social status. However, a misinterpretation of siri’, known as “masiri”, has emerged, where excessive consumption is driven by the desire to maintain social image or avoid being looked down upon. From the perspective of Islamic economics, the consumption practices of the Bugis Muslim community in Watampone do not fully reflect the principles of halal, thayyib (good and wholesome), non-israf (non-excessive), and iqtishad (balanced living). A tension is evident between cultural values and religious principles, especially when siri’ is understood superficially and focused solely on external validation. This study recommends a recontextualization of siri’ in harmony with Islamic values, so that local culture can continue to serve as a moral foundation in economic life.